Pelatihan Keterampilan Dasar Dunia Kerja Bagi Siswa SMK - Fahmi Susanti; Farhan; Yusuf Orlando; Asultoni Imam Hidayat (Advances In Education Journal, 2025)
The Community Service Program titled “Teamwork in the Workplace” was conducted to enhance the understanding of high school and vocational school students regarding the importance of teamwork in the modern work era. In reality, many individuals face various challenges such as differences in personality, inefficient communication, and internal conflicts that may disrupt team performance. Through this program, participants gain insights into the significance of teamwork in achieving organizational goals, and they are also equipped with effective communication skills, mutual respect, trust among team members, and conflict-handling abilities. The implementation of this program is carried out through interactive seminars and discussion sessions, allowing participants to experience firsthand the development of teamwork skills. It is expected that this activity can help shape participants’ character to become more prepared for a competitive, adaptive, and collaboration-focused work environment.